Oksigenasi dengan Bag and Mask 10 LPM Memperbaiki Asidosis Respiratorik - Sunarko Setyawan; Tintin Sukartini; Sriyono Sriyono; Kusmiati Kusmiati (Jurnal Ners, 2007)
Introduction: ALO (Acute Lung Oedema) is the most common and remarkably life threatening medical emergency. It is not unusual that clients come to the hospital in critical condition. ALO occurs due to fluid accumulation in the alveoly, thereby impairing gas exchange and the client will experience respiratory acidosis and hypoxemia. The ALO management that must be urgently carried out is high concentration oxygenation with PEEP (Positive End Expiratory Pressure) to prevent alveolar collapse by means of Bag and Mask oxygenation, CPAP (Continous Positive Airway Pressure) mask and mechanical ventilation. The objective of this study was to explain the effect of oxygenation by using 10 lpm (liters per minute) bag and mask on respiratory acidosis improvement in ALO client. Method: A pre-experimental one group pre post test design was used in this study. The population were all ALO clients in ICU (Intensive Care Unit), Adi Husada Kapasari Hospital. There were 12 respondents which taken by using total sampling. Data were collected by using observation on the blood gas analyze (pH, PaCO2 and PaO2) then analyzed by using Paired t-Test with significance level a≤0.05. Result: The result showed that 12 respondents experienced respiratory acidosis and hypoxemia before intervention with 10 lpm bag and mask oxygenation was gave to them. After intervention for 1 hour, the result showed that pH increased (p=0.003), PaCO2 reduced (p=0.004) and PaO2 increased (p=0.005). Discussion: It can be concluded that 10 lpm bag and mask oxygenation had significance effect on the improvement of respiratory acidosis in ALO clients. Further studies should involve more respondents and more reliable measurement tools to obtain better accuracy.